2020
DOI: 10.1080/1743727x.2020.1791071
|View full text |Cite
|
Sign up to set email alerts
|

Studying classroom climate effects in the context of multi-level structural equation modelling: an application-focused theoretical discussion and empirical demonstration

Abstract: The present article focuses on classroom climate effects in the context of multi-level structural equation modelling. We first discuss the need to appropriately model classroom climate as a classroom-level construct. We then analyse the effects of classroom climate (academic goal structures and social goal structures) on students' motivation in terms of achievement goals (mastery goals) in an empirical demonstration. This study relies on doubly latent multi-level structural equation modelling and draws on a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Educational systems such as schools are multilevel systems ( Kozlowski and Klein, 2000 ) in which students are grouped into classes and share similar experiences. At the class level, perceived peer and teacher support constitute the class climate, which, when analyzed, must be treated as a class-level construct ( Lüdtke et al, 2009 ; Bardach et al, 2020 ). The classroom climate is a common characteristic that all students in a class are exposed to.…”
Section: Introductionmentioning
confidence: 99%
“…Educational systems such as schools are multilevel systems ( Kozlowski and Klein, 2000 ) in which students are grouped into classes and share similar experiences. At the class level, perceived peer and teacher support constitute the class climate, which, when analyzed, must be treated as a class-level construct ( Lüdtke et al, 2009 ; Bardach et al, 2020 ). The classroom climate is a common characteristic that all students in a class are exposed to.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, features of the educational context (i.e., adaptive prerequisites) are usually captured by aggregated classroom and school variables (Lüdtke et al, 2008;Marsh et al, 2012;Bardach et al, 2020). For example , Morin et al (2014) demonstrated that aggregated classroom climate (i.e., classroom goals, challenge, teacher caring) had positive effects on students' self-efficacy.…”
Section: Learning Environments As Distinctive Precursors Of Motivationmentioning
confidence: 99%
“…Zusätzlich wurde für Leistung (latenter Faktor aus den letzten Zeugnisnoten in den Hauptfächern Deutsch, Mathematik, Englisch) bei akademischem Selbstkonzept und schulischem Wohlbefinden kontrolliert. In allen Analysen wurde die hierarchische Datenstruktur (Schüler*innen genestet in Klassen) mit Hilfe von clusterrobusten Standardfehlern berücksichtigt (Bardach et al 2020).…”
Section: Messinstrumenteunclassified